VizWick: a multiperspective view of hierarchical data - Burch, Michael; Vramulet, Adrian; Thieme, Alex; Vorobiova, Alina; Shehu, Denis; Miulescu, Mara; Farsadyar, Mehrdad; van Krieken, Tar (VINCI'20: Proceedings of the International Symposium on Visual Information Communication and Interaction, 2020)
In this paper we present a web-based interactive tool for visualizing hierarchical data. Our main purpose is to facilitate the visualization of datasets. We achieve this by offering VizWick in a browser environment, with no requirement of additional software. We provide the option to view the same dataset from multiple coordinated perspectives, thus providing the possibility to gain more analytical insight than if the dataset was visualized in a single view. We focus on several hierarchy visualization techniques which can be either in 2D, 3D, or a virtual reality environment. The choice of programming language is JavaScript, with the aid of PixiJS and Three.js libraries. We demonstrate the usefulness of our tool by applying it to the NCBI taxonomy, a hierarchically structured dataset which contains over 300,000 elements.